Long-term efficacy and safety of rilpivirine plus abacavir and lamivudine in HIV-1 infected patients with undetectable viral load. - Nadia Galizzi; Laura Galli; Andrea Poli; Nicola Gianotti; Elisabetta Carini; Alba Bigoloni; Giuseppe Tambussi; Silvia Nozza; Adriano Lazzarin; Antonella Castagna; Daniela Mancusi; Roberta Termini (PLoS ONE, 2018)
A regimen with rilpivirine (RPV), abacavir (ABC) and lamivudine (3TC) is simple and may allow the sparing of tenofovir and protease inhibitors. However, data on use of this combination as a strategy of switch are limited. Aims of the study were to assess the long-term efficacy and safety of this regimen.Retrospective study on HIV-1 infected patients followed at the Infectious Disease Department of the San Raffaele Scientific Institute, HBsAg-negative, HLA B5701-negative, with no documented resistance to RPV, ABC and 3TC, with HIV-RNA<50 copies/mL who started RPV plus ABC/3TC from March 2013 to September 2015. The primary outcome was durability [no treatment failure (TF)]. Secondary objectives were to evaluate changes in immunological, metabolic and other safety parameters. TF was defined as the occurrence of virological failure (VF, 2 consecutive values >50 copies/mL) or discontinuation of any drug in the regimen for any reason. Patients' follow-up accrued from the date of RPV plus ABC/3TC initiation to the date of TF (VF or discontinuation of any drug in the regimen) or to the date of last available visit. Time to TF was evaluated by use of the Kaplan-Meier curves. Mixed linear models were applied to evaluate changes in immunological, metabolic and other safety parameters.In this analysis, 100 patients starting RPV plus ABC/3TC were included. By 12, 24 and 36 months after switching to RPV plus ABC/3TC, the proportions of individuals without TF were 88% [95% confidence interval (CI): 79%-93%], 82% (95% CI:73%-89%) and 78% (95% CI:68%-86%), respectively. Time to TF was not significantly influenced by CD4+ nadir (≤200 vs >200 cells/μl; log-rank test: p = 0.311) or pre-ART viral load (<100000 vs ≥100000 copies/mL; log-rank test: p = 0.574) or the type of previous antiretroviral regimen (PI+2NRTIs vs NNRTI+2NRTIs vs Other; log-rank test: p = 0.942). Over a median follow-up of 2.9 years (IQR: 1.9-3.5), 26 subjects discontinued the treatment [10 due to toxicity, 7 for interactions with other drugs, 3 due to cardiovascular risk concern, 2 due to single viral blip, 1 due to VF, 1 for asthma, 1 patient's decision, 1 due to enrolment in a study protocol].In this retrospective study, long-term use of RPV plus ABC/3TC regimen is effective and safe. Efficacy of this regimen was not found to be affected by low CD4+ nadir or high pre-ART viral load.